(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Guduchi/Giloy (Tinospora cordifolia) is declared a national herb of India due to its multiple medicinal properties. Samsamani Vati is also known as Guduchi ghanavati (a concentrated form of decoction of Guduchi stem) the secondary Kalpala (formulation) derived from the primary Kwatha Kalpana (decoction). Samsamani Vati is freely distributed by the Ministry of AYUSH in all states and union territories of India as prophylaxis for COVID-19. The molecular docking of Tinocordicide - a constituent of Guduchi (Tinospora cordifolia) showed significant interruption of the viral RBD and host ACE2 interactions. T. cordifolia, T. crispa, T. sinensis, T. smilacina, T. bakis, and T. sagittata are different species of Guduchi, whereas Tinospora crispa and T.sinensis are hepatotoxic. General people are aware of the use of Samsamani vati/ Guduchi Ghana vati/Giloy and purchase from leading Ayurveda medicine manufacturers in India. Tinosporaside is an immune-modulatory active compound as well as a cholinergic inhibitor. It is an attempt for compare analysis of Samsamani Vati/Guduchi Ghana vati used in the population for the prevention of COVID-19 of government supply and lead Pharmaceutical Company of India. The Samsamani Vati/Guduchi Ghana vati of lead Ayurveda Pharmaceutical and Government Supply. (Dabur, Zandu, Patanjali, Himalaya, Baidyanath and IMPCL) were purchased from the local market and put forth for analysis. Tinosporide is significantly detected in Patanjali, Zandu and IMPCL-manufactured Samsamani Vati, whereas a trace amount of bioactive compound in Dabur and not detected in Baidyanath. The analysis showed that no uniformity of Samsamani Vati/Guduchi Ghana Vati of the competitive brand of India. It is recommended to maintain uniformity of bioactive molecules not only for desired efficacy but also for safety.